SOME RESULT IN THE EXISTENCE, UNIQUENESS AND STABILITY SOLUTION OF INTEGRO-DIFFERENTIAL EQUATION - ABDI, SAHLA BIBO; BUTRIS, RAAD NOORI (E-Jurnal Matematika; Vol 13 No 2 (2024), 2024)
The purpose of this paper is to investigate the existence, uniqueness, and stability   solution to a non-linear system of integro-differential equations by using both methods Picard approximation and Banach fixed point theorem.  The existence, uniqueness, and stability   theorems are established under necessary and sufficient conditions of closed and bounded domain.